Capital Controls and the Icelandic Banking Collapse: An Assessment - Mccombie, John Stuart Landreth; Spreafico, Marta (Palgrave Macmillan, 2016)
This chapter assesses the causes and consequences of the Icelandic banking collapse of 2008. It examines the reasons behind the rapid growth of the banks over the subsequent few years following their privatization, the lack of prudential regulation and the high-risk loan strategy of the banks. These, together with the failure of the Central Bank of Iceland to act as a lender of last resort of foreign currency, made the collapse of the financial system almost inevitable. The IMF was called in and a notable aspect of its rescue package was the imposition of capital controls. This can be seen as the culmination of a secular change of the IMF’s attitude to the regulation of cross-border financial flows. The chapter presents an assessment of how effective this strategy has been. It concludes with a more general discussion of the political economy of capital controls.